Prediksi Penjualan Sparepart Mobil Terlaris Menggunakan Metode K-Nearest Neighbor - Sahara Abdy; Erika Roberta Br Gultom; Sri Ramadhany; Afifudin Afifudin (JURIKOM (Jurnal Riset Komputer), 2022)
PT. GAYA MAKMUR MULIA MEDAN is a company engaged in selling spare parts and spare parts in North Sumatra. Along with the development of technology, the increasing business competition, especially regarding the sale of spare parts. This also affects the competition between brands of goods with the quality they produce. Products offered by various brands, brands influence people to buy these products. Judging from the large number of consumer requests for spare parts products based on sales over the last 2 years, predictions are needed for sales of the best-selling spare parts products, in order to make it easier for companies to provide stock. To find out the sales of best-selling spare part product, data mining techniques and K-Nearest neighbor algorithm are used to produce predictions of the best-selling sales in the Mitsubishhi division with an accuracy of 80,00% and Isuzu accuracy of 66,67% so that acquisition targets are obtained to increase the accuracy value for the classification of best-selling product sales.PT. GAYA MAKMUR MULIA MEDAN is a company engaged in selling spare parts and spare parts in North Sumatra. Along with the development of technology, the increasing business competition, especially regarding the sale of spare parts. This also affects the competition between brands of goods with the quality they produce. Products offered by various brands, brands influence people to buy these products. Judging from the large number of consumer requests for spare parts products based on sales over the last 2 years, predictions are needed for sales of the best-selling spare parts products, in order to make it easier for companies to provide stock. To find out the sales of best-selling spare part product, data mining techniques and K-Nearest neighbor algorithm are used to produce predictions of the best-selling sales in the Mitsubishhi division with an accuracy of 80,00% and Isuzu accuracy of 66,67% so that acquisition targets are obtained to increase the accuracy value for the classification of best-selling product sales.